Edukasi Perilaku Stres Masyarakat Usia 18-22 Tahun Dengan Raising Awareness Melalui Online Campaign - Febryani Suryaning Putri; Katmini Katmini (Poltekkes Kemenkes Surakarta, 2021)
Background: The COVID-19 pandemic is currently influencing many aspects of life. The pressure is experienced by all societies impacted by the pandemic, causing physiological and psychological reactions. Stress is produced by emotional problems induced by excessive pressure. If stress is experienced on a regular basis, it can lead to painful emotional conditions such as depression and anxiety. Raising awareness of the stressful behavior is one of the preventive interventions needed to cope with stress. It is expected that people aged 18-22 years will be able to manage with their own pressure after obtaining stress education and health promotion. Methods: The target needed is to educate people aged 18-22 years by distributing leaflets online through social media on June 9, 2021. After distributing the leaflets, it is hoped that the respondents will provide feedback by filling out the questionnaires that we distribute. Results: The online awareness campaign has been a success. 53 respondents aged 18-22 replied to the questionnaire after obtaining information through leaflets. As a result, most people react to the present pandemic is increasing stress levels. Conclusion: Stress concerns can be prevented with education that raises awareness of stress behavior.